1997
DOI: 10.1159/000237487
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Thromboxane A<sub>2</sub> in Antigen-Induced Nasal Blockage in Guinea Pigs

Abstract: To estimate the involvement of thromboxane (Tx) A2 in the onset of nasal blockage, we examined the effect of the selective TxA2 receptor antagonist, S-1452, as well as an H1-antihistamine, diphenhydramine, on the antigen-induced increase in intranasal pressure, as an index of nasal blockage, in anesthetized guinea pigs actively sensitized by inhalation of aerosolized ovalbumin (OA). Oral administration of S-1452 or intravenous administration of diphenhydramine significantly but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…When orally administered to guinea pigs 2 h before antigen exposure, S-1452 significantly inhibited antigeninduced plasma exudation into both the nasal mucosa and nasal airway lumen. In this model, we have reported that the level of TxB 2 was significantly elevated in nasal lavage fluid after antigen exposure [11]. These findings suggest that TxA 2 is involved in antigen-induced nasal plasma exudation in this model.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…When orally administered to guinea pigs 2 h before antigen exposure, S-1452 significantly inhibited antigeninduced plasma exudation into both the nasal mucosa and nasal airway lumen. In this model, we have reported that the level of TxB 2 was significantly elevated in nasal lavage fluid after antigen exposure [11]. These findings suggest that TxA 2 is involved in antigen-induced nasal plasma exudation in this model.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, we examined the involvement of histamine in antigen-induced nasal plasma exudation, using an H 1 -antihistamine, diphenhydramine. Intravenous administration of diphenhydramine (5 mg/kg) 5 min before antigen exposure markedly suppressed dye exudation into the nasal mucosa and nasal lavage fluid with the percent inhibition of about 80-90%, indicating that histamine, as well as TxA 2 , acts as a major mediator for inducing nasal plasma exudation, but does not for increasing intranasal pressure [11], following antigen challenge in this guinea pig model. These pharmacological studies showing the marked suppression of the antigen-induced nasal plasma exudation by either S-1452 or diphenhydramine further suggest that TxA 2 and histamine synergistically cause increase in vascular permeability, i.e., TxA 2 may contribute to nasal plasma exudation via enhancing vascular permeability caused by histamine as well as via directly inducing plasma exudation.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations